2015
DOI: 10.1084/jem.20121878
|View full text |Cite
|
Sign up to set email alerts
|

Blocking follistatin-like 1 attenuates bleomycin-induced pulmonary fibrosis in mice

Abstract: Follistatin-like 1 (Fstl1) is induced in response to lung injury and promotes the accumulation of myofibroblasts and subsequent fibrosis via regulation of TGF-β and BMP. Reducing Fstl1 in mice reduces bleomycin-induced fibrosis in vivo, offering a potential therapeutic target for progressive lung fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
172
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(185 citation statements)
references
References 58 publications
(103 reference statements)
11
172
2
Order By: Relevance
“…FSTL1 can activate and increase the expression of TGFβ41. In the present study, we observed that TGFβ, total Smad2/3 and p-Smad2/3 protein levels were increased by exogenous FSTL1 administration.…”
Section: Discussionsupporting
confidence: 63%
“…FSTL1 can activate and increase the expression of TGFβ41. In the present study, we observed that TGFβ, total Smad2/3 and p-Smad2/3 protein levels were increased by exogenous FSTL1 administration.…”
Section: Discussionsupporting
confidence: 63%
“…5c). This is also in agreement with our recent study using a bleomycin mouse model 24 and suggests that the restored TGF-β1/BMP balance may be the molecular underpinnings for the attenuated fibrogenesis in Fstl1 +/− mice.
Figure 5Fstl1 modulates myofibroblast differentiation via facilitating TGF-β1 signaling. ( a ) qRT-PCR analysis of TGF-β1 mRNA expression in lung tissues of Fstl1 +/− and WT mice at indicated time after saline or silica exposure (n = 4 per group; * P  < 0.05 by one-way ANOVA followed by Student’s t test).
…”
Section: Resultssupporting
confidence: 90%
“…Our study is the first to use conditional inactivation of Fstl1 in macrophage/myeloid cells to study its influence on a disease phenotype in vivo. Recent studies have used heterozygous Fstl1 +/− deficient mice to demonstrate that inhibiting Fstl1 does not inhibit lung inflammation, but does attenuate bleomycin induced pulmonary fibrosis in mice through a TGFβ dependent pathway 28 . In the study of bleomycin induced pulmonary fibrosis, the cellular source of Fstl1 was fibroblasts 28 a well known mesenchymal source of Fstl1 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have used heterozygous Fstl1 +/− deficient mice to demonstrate that inhibiting Fstl1 does not inhibit lung inflammation, but does attenuate bleomycin induced pulmonary fibrosis in mice through a TGFβ dependent pathway 28 . In the study of bleomycin induced pulmonary fibrosis, the cellular source of Fstl1 was fibroblasts 28 a well known mesenchymal source of Fstl1 5 . Our study differs from the study of bleomycin induced pulmonary fibrosis in that we demonstrate that in chronic allergen induced asthma, non-mesenchymal cells such as macrophages (not considered a significant source of Fstl1) are a significant source of Fstl1, that inhibiting Fstl1 inhibits allergen induced airway eosinophilic inflammation (no effect on inhibiting bleomycin induced lung inflammation), and that the downstream pathway of Fstl1 in macrophages is OSM (in bleomycin model it is TGFβ).…”
Section: Discussionmentioning
confidence: 99%